SELF-ESTEEM SCALE FOR ADOLESCENTS: ELABORATION AND PSYCHOMETRIC ANALYSIS - Cerna Dorregaray, Orlando (2020)
This study refers to the development and psychometric analysis of a self-esteem scale for adolescents. The theoretical basis is from Clemens (1995) who argues that self-esteem is the satisfaction we feel of ourselves when we have been able to meet four basic needs: bonding, uniqueness, power and guidelines. The scale was subjected to rigorous validity and reliability análisis. It is a pure investigation because its purpose is to contribute new knowledge with the objective of providing greater foundations to the theory proposed by Clemens (1995). The design is correlational and comparative descriptive. The scale was applied to 760 adolescents. The sample is not intentional probabilistic, consisting of students from first to fifth year of high school in three schools in Lima. The instrument that was built was a Likert scale to assess self-esteem according to the theoretical proposal. Content validity analyzes have been satisfactory. The Aiken V concordance indexes obtained were highly satisfactory. The indexes of internal consistency of the inventory, as well as the indices of correlation between them, have indicated high values of the Cronbach Alpha and Omega of McDonald aceptable. The Cronbach and Omega McDonald coefficients for each of the four dimensions of the scale have high values. Cronbach's Alpha coefficient showed very high values. In conclusion, the self-esteem scale for adolescents presents sufficient evidence of validity and reliability that makes it a satisfactory measure to assess self-perception of the adolescent's personal worth.